Factors Affecting the Implementation of SISRUTE Version 2 as Referral System by Public Health Center in Kediri City - Aris Andrianto; Reny Mareta Sari (Universitas STRADA Indonesia, 2025)
The referral system is a crucial component of healthcare services to ensure patients receive optimal care. The Sisrute version 2 application is expected to improve the efficiency of referrals from Puskesmas to higher-level health facilities. This study aims to analyze the factors influencing the implementation of Sisrute version 2 by Puskesmas in Kediri City using a quantitative approach with Pearson correlation analysis. A total of 65 healthcare workers participated as respondents. The results showed that leadership support (r = 0.578, p < 0.01), communication networks (r = 0.368, p < 0.01), staff motivation (r = 0.284, p < 0.05), and training (r = 0.368, p< 0.01) had significant relationships with Sisrute implementation. Meanwhile, gender, education, and age were not significantly related. In conclusion, the successful implementation of Sisrute version 2 is influenced by leadership support, networks, motivation, and training. Strengthening these factors through supportive policies and competency development can enhance referral system effectiveness.